Genetic and phenotypic differentiation among Galaxias maculatus populations in a Patagonian postglacial lake system - Carrea, Cecilia (2012)
Understanding the influence of landscape features on population differentiation is fundamental to evolutionary biology studies. We examined spatial patterns of genetic and phenotypic variability among Galaxias maculatus populations in a complex of four postglacial lakes in northwestern Patagonia differing in size and connectivity among them. A hierarchical Bayesian analysis grouped the individuals collected from eleven localities into three genetic clusters, first defining the populations of the two large lakes and separating the two small lakes in subsequent analysis. Genetic structuring was restricted within large lakes. It is known that the larval stage of Galaxias maculatus migrate to the limnetic zone of Patagonian lakes, possibly exerting an homogenizing effect on gene flow within lakes. Gene flow asymmetry and divergences among lakes can be explained by a combination of landscape characteristics and the presence of predators in the short streams that connect them. Individuals from the small lakes are the most divergent morphologically and genetically. The population in the isolated Redonda Lake, exhibits meristic differences as well, suggesting strong drift and environmental effects. This population is likely to have been isolated following the decline in water level of a paleolake that existed in this region approximately 13.2kya BP. © 2012 The Linnean Society of London.